Reproduction, denning ecology, and behavior of the San Clemente Island fox (Urocyon littoralis clemente) - Gould, Nicholas Paul, author; Andelt, William F., advisor; Clements, William, committee member; Ghalambor, Cameron, committee member; Stanley, Thomas R., committee member (Colorado State University. Libraries, 2010)
Island foxes (Urocyon littoralis) have experienced severe reductions in populations on 4 of 6 California Channel Islands. While numbers of San Clemente Island (SCLI) foxes (Urocyon littoralis clemente) have remained relatively stable, additional data on reproductive success in urban and rural areas is necessary so that we can better manage the population if it sustains declines. We also need to know locations and characteristics of den sites in order to minimize possible impacts of military training activities on foxes. I found that 5 of 6 urban females and 5 of 11 rural females produced at least 19 kits on the northern 2/3 of SCLI during 2008. Although foxes in urban areas may be reproducing more successfully than foxes in rural areas, urban foxes often selected den sites near roads which may expose them to increased mortalities. I located 23 den sites, on an average of 17-18° slopes with 40% having westerly-facing aspects. I recommend redirecting ground-disturbing military training maneuvers away from these areas during February through June which may minimize impacts of training activities on foxes. Collisions with vehicles have created concern for the welfare of the endemic San Clemente Island fox. The small population on the northern 2/3 of SCLl has sustained an estimated annual mortality rate of 3-8% due to collisions with vehicles from 2000 through 2007. To identify potential management solutions for minimizing these mortalities, I examined behavioral responses of SCLI foxes to approaching vehicles on roads. 1 found that during 67% of 541 observations, foxes remained within 5 m of an approaching vehicle, and during 26% of 258 observations, foxes remained on the road as the vehicle passed suggesting many foxes were naive toward vehicles. During 8% of 258 observations, foxes remained in the center of the road; thus, we were required to stop our vehicle to avoid hitting the fox. I examined 5 main behaviors (running, walking, sitting, standing, and foraging) of foxes as a vehicle approached to ascertain if behaviors of foxes changed with distance. Foxes showed no trend towards avoidance behaviors (running or walking away) at closer distances (0, 5, 25 m) to the approaching vehicle. During 49 of 150 observations where foxes exhibited directional movements in response to our vehicle at 0, 5, 25, 50 and 100 m, foxes approached our on-coming vehicle, further suggesting SCLI foxes exhibit naive behaviors toward vehicles. I found no significant effects of road surface, biological season, day versus night, and foxes in urban versus rural areas on behaviors. I recommend educating drivers on SCLI about the general lack of vehicle avoidance behaviors of foxes, and recommend reducing the speed limit to minimize impacts of vehicles on island foxes.
Covers not scanned.
Keywords: Island gray fox -- Ecology -- California -- San Clemente Island; Island gray fox -- Behavior -- California -- San Clemente Island